Flare-Up of Rheumatoid Arthritis by Anti-CTLA-4 Antibody but Not by Anti-PD1 Therapy in a Patient with Metastatic Melanoma - Nicoletta F. Jaberg-Bentele; Michael Kunz; Shatha Abuhammad; Reinhard Dummer (Karger Publishers, 2017)
A 47-year-old female patient with rheumatoid arthritis (RA) treated with methotrexate, was diagnosed with metastatic melanoma. After surgical removal of the tumor, the patient started treatment with ipilimumab while methotrexate was stopped. One week after initiation of ipilimumab, the patient developed typical symptoms of RA. Analgetic therapy was started. After 4 cycles of ipilimumab, melanoma progression was radiologically evident. The treatment plan was changed to pembrolizumab (anti-PD1 antibody), and the patient did not show active signs of RA anymore. Despite treatment with pembrolizumab, the patient died 4 months later due to tumor progression. The exact mechanism by which ipilimumab (anti-CTLA-4 antibody) provoked RA symptoms is still not fully understood. This subject needs more investigation, especially in an era in which immunotherapies are a standard therapy for patients with malignancy.